2006
DOI: 10.1007/s00520-006-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition intervention using an eicosapentaenoic acid (EPA)-containing supplement in patients with advanced colorectal cancer. Effects on nutritional and inflammatory status: a phase II trial

Abstract: Dietary counseling and the provision of EPA-ONS may result in maintenance of nutritional status and QOL, however randomized trials are required to evaluate the impact of EPA on toxicity from chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 27 publications
(27 reference statements)
6
105
1
5
Order By: Relevance
“…It has been reported that nutritional management is important in HOI treatment (7,8). Recent studies have reported that ProSure™ (Abbot Japan Co., Ltd, Tokyo, Japan), an EPA-containing supplement, affects the nutritional status and quality of life in advanced cancer patients (17,18). ProSure™ was introduced in postoperative nutritional management and the ileostomy output was examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nutritional management is important in HOI treatment (7,8). Recent studies have reported that ProSure™ (Abbot Japan Co., Ltd, Tokyo, Japan), an EPA-containing supplement, affects the nutritional status and quality of life in advanced cancer patients (17,18). ProSure™ was introduced in postoperative nutritional management and the ileostomy output was examined.…”
Section: Discussionmentioning
confidence: 99%
“…(42). Read et al (43) indicated that after an average amount of 408 ml/day EPA for 3 weeks, a significant increase was noted in mean patient weight (2.5 kg) (p=0.03), and LBM was maintained. In the summary of this study, it was stated that dietary counseling by suitably qualified dietitians and the administration of EPA in patients with advanced colerectal cancers receiving chemotherapy, help to maintain weight and possibly improve symptom control, nutritional status and QoL.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…48 According to a recent systematic review, malnourished cancer patients, receiving nutritional counseling along with or without ONS resulted in nutritional status improvements. 49 Body weight increase in cancer patients consuming ONS leads to maintenance of lean body mass and better quality of life 50 . Better nutritional status among head and neck as well as gastrointestinal tract cancer patients consuming ONS compared to patients receiving standard care has been reported earlier.…”
Section: Nutrition Intervention and Its Benefitsmentioning
confidence: 99%